Social Protection and Cash Transfers in Mozambique: Between international consensus and local agency - Maria Clara Oliveira; Teresa Almeida Cravo (Cadernos de Estudos Africanos)
This article examines the rise of cash transfer programs and their embrace, since the 1990s, as a central element in global public policy on economic and social development and poverty reduction. Focusing on the example of Mozambique, an early adopter of such programs, it analyses the relationship between international organizations, development aid agencies, national government and local agents in the field, in the design and delivery of social protection policy. While external actors have been important in shaping Mozambican public policy, this study reveals the relevant role played by the country’s domestic actors in agenda-setting, conception and implementation of a cash transfer program as early as 1990, and its evolution over the subsequent three decades. In this interplay between international and local levels of decision- and policy-making, the article looks into the barriers to the program’s reach, pace and limited impact.